Legacies of Enlightenment: Diderot’s La Religieuse and Its Cinematic Adaptations - Wyngaard, Amy (Lumen)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 2021)
La Religieuse is a classic French Enlightenment work in its elucidation of forced religious vocation as well as the hypocrisy and abuses of the Catholic Church. In reviving and effectively re-envisioning the novel, filmmakers Jacques Rivette and Guillaume Nicloux succeed in bringing Diderot’s ideas to bear on contemporary issues such as the image and role of the Church post Vatican II, and the effects of patriarchal and religious oppression on the individual. This article examines the context and reception of all three works (the original text and two film adaptations) and their engagement with specific historical circumstances as well as more universal concerns; by extension, this project represents an effort to probe the perhaps unexpected, continued interest in Diderot’s writings in popular culture today. An analysis of the literary and cinematic posterity of La Religieuse underscores the ongoing pertinence of French Enlightenment thought while illuminating the linked political and aesthetic inheritance of Diderot’s novel.